Impact of the COVID-19 Pandemic on the Diagnosis of Tuberculosis in Brazil - Souza, Mariana do Rosário (2022)
Publisher Copyright: Copyright © 2022 Souza, Paz, Sales, Jesus, Tavares, Lima, Sousa, Melo, Carmo, Souza and Bezerra-Santos.